Exploring enhanced menu labels' influence on fast food selections and exercise-related attitudes, perceptions, and intentions. (1st October 2016) - Lee, Morgan S.; Thompson, Joel Kevin
Abstract: Labeling restaurant menus with calorie counts is a popular public health intervention, but research shows these labels have small, inconsistent effects on behavior. Supplementing calorie counts with physical activity equivalents may produce stronger results, but few studies of these enhanced labels have been conducted, and the labels' potential to influence exercise-related outcomes remains unexplored. This online study evaluated the impact of no information, calories-only, and calories plus equivalent miles of walking labels on fast food item selection and exercise-related attitudes, perceptions, and intentions. Participants ( N  = 643) were randomly assigned to a labeling condition and completed a menu ordering task followed by measures of exercise-related outcomes. The labels had little effect on ordering behavior, with no significant differences in total calories ordered and counterintuitive increases in calories ordered in the two informational conditions in some item categories. The labels also had little impact on the exercise-related outcomes, though participants in the two informational conditions perceived exercise as less enjoyable than did participants in the no information condition, and trends following the same pattern were found for other exercise-related outcomes. The present findings concur with literature demonstrating small, inconsistent effects of current menu labeling strategies and suggest that alternatives such as traffic light systems should be explored.